ANALISA DISTRIBUSI TEMPERATUR KOMPOR SERBUK KAYU AKIBAT PENAMBAHAN DINDING API (FIRE WALL) DENGAN MENGGUNAKAN INFRARED THERMOGRAPH - Helen Riupassa; Hendry Y. Nanlohy (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Sains dan Teknologi Jayapura, 2014)
Household sector as the second largest energy user after the industrial sector, thereality of what happened in Papua subsidized price of kerosene has reached Rp 6,000 - Rp10,000/liter due to government policy. Wood processing industry produces 40% of woodwaste which cause problems that impact on the environment. Need to use it into valueadded products, one of them as an alternative energy source to help alleviate the localeconomy.The method used in this study is an experimental analysis, by comparing the stovewithout the firewall and the firewall, and the temperature distribution was taken usinginfrared thermograph, and the other to obtain temperature data used infrared thermometer.The results of this study showed the exit temperature (out) with firewalls tend to behigher (591,1°C) compared with no firewall (583°C), because the firewall to isolate heat sothat the heat of combustion are all routed through the firewall to the outside of the pan isreinforced with color degradation results thermograph. But without the firewall and thetemperature rising back tends to decline because of the longer sawdust burning to ashes sothat has not been burned sawdust automatically drops down so that the distance of the potwith the heat source and the heat of combustion is much spread do not like using a firewall